Mamma mia! : here we go again [videorecording (DVD)] - Parker, Ol, 1969-; Parker, Ol, 1969-; Seyfried, Amanda; James, Lily, 1989-; Garcia, Andy (Universal Pictures Home Entertainment, 2018)
As Sophie prepares for a hotel re-opening, she reflects on her mother's journey in life and realizes they are similar in unexpected ways.